Evaluation of Magnetic Resonance Imaging (MRI) Findings following posterior Sagital Ano-Recto Plasty (PSARP) in Severe Incontinent Children with High Imperforate Anus (IA) - Bijan Ziyaee; Masoud Nazem; Maryam Riahinezhad; Mehrdad Hosseinpour (Advanced Biomedical Research, 2023)
Background: The aim of this study was to evaluate pelvic MRI accuracy for measurement of anatomical land marks in severe fecal incontinent (FI) children with high imperforate anus (IA). Materials and Methods: A total of 80 children (40 cases and 40 controls) aged more than 4 years with severe FI were assessed. Magnetic resonance imaging was performed by a radiologist with the same device. For pelvic anatomical land marks measurement, we measured the ano-rectal angel and hiatal/pc ratio. Results: The mean of ano-rectal angel was 118.67 ± 25.2 mm in cases and 132.07 ± 13.8 mm in control group (P = .004). H/PCR was 0.63 ± 0.05 in cases and 0.62 ± 0.45 in controls (P = NS). There was no significant correlation between [INSIDE:1] (r = 0.25, P = 0.36) or ano-rectal angle measurement (r = 0.16, P = 0.05) and FI score in patients with severe FI. Conclusions: Pelvic magnetic resonance imaging could be accurately used is measuring the ano-rectal angle is high IA children with severe FI which leads to selected patients who may have benefits of reoperation.